Legislação indigenista e políticas indígenas no século XIX : a ocupação dos territórios dos Kadiwéu (Mbayá-Guaykuru) e dos Terena (Chané-Guaná) - Rodrigues, Valéria Nogueira (2021)
The objective of this thesis is to investigate the main premises of the indigenist policy imposed on indigenous peoples, emphasizing the issue of dispute over the possession of their traditional territories. Through the trajectory of the Kadiwéu (Mbayá-Guaykuru) and Terena (Chané-Guaná) I seek to reflect the role of these indigenous peoples in the game of unequal forces that was established from non-indigenous presence in their territories. I demonstrate how the Mbayá-Guaykuru and Chané-Guaná groups maintained their own policy on the region invaded by the Spanish and, later, by the Portuguese. I treat the Chaco/Pantanal “system”, firstly as a space for experiences and disputes between different indigenous groups, with its own socio-environmental dynamics and, later, after the European intrusion, as a colonial space, with a violent logic of transforming indigenous territories into lands, properties, imposing an economic and political order that reduced indigenous spaces by corralling them into small swaths of their territories. I reflect on the transformation of indigenous territories into private property, a process that began in the colonial period and intensified under the Empire. As indigenous policies, I highlight the role played by indigenous people. This perspective opens space to discuss Indigenous Protagonism and Decoloniality as theoretical tools for reinterpreting the role that indigenous people played in historical processes and historiography. Lastly, I analyze the process of occupation of Mato Grosso from the perspective of conflicts over land tenure. Colonial and imperial indigenist legislation can be observed in the official documentation produced by the administrative apparatus and expresses the general ideology outlined by the metropolitan policy. The interiorization process made it possible for the Lusitanian to reach the region we know today as the State of Mato Grosso. The history of this region is marked by the invasion and dispute of territories through an aggressive policy towards the indigenous people. The 18th century was the period of institution of the metropolitan administrative political apparatus and the formation of a politically and economically dominant class forming a local elite with great political force capable of manipulating and conducting the process of access to land according to its own interests and with great damage to the indigenous peoples who already inhabited the region. In the XIX century, the agrarian policy and the indigenist policy adopted point to the search for centralization of power by the State through the monopolization of land. Although it wanted to discriminate between public and private lands to secure them, the State allowed various means of fraud to regularize land acquired irregularly, favoring the concentration of land in the hands of local elites. In general, this situation has had and still has a negative impact on indigenous peoples deprived of their material and symbolic assets, even though official legislation guarantees the possession of traditional territories.